2014
DOI: 10.1002/cmdc.201402292
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of N‐Acylated Aza‐Goniothalamin Derivatives and Evaluation of Their in vitro and in vivo Antitumor Activity

Abstract: Herein we describe the synthesis of a focused library of compounds based on the structure of goniothalamin (1) and the evaluation of the potential antitumor activity of the compounds. N-Acylation of aza-goniothalamin (2) restored the in vitro antiproliferative activity of this family of compounds. 1-(E)-But-2-enoyl-6-styryl-5,6-dihydropyridin-2(1H)-one (18) displayed enhanced antiproliferative activity. Both goniothalamin (1) and derivative 18 led to reactive oxygen species generation in PC-3 cells, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 79 publications
2
31
0
2
Order By: Relevance
“…Regarding natural product‐derived compounds, different studies have shown an antitumoral activity in different cancer cell lines treated with compounds such as GTN (de Fátima et al, ). Barcelos et al () verified that compounds derived from GTN presented antiproliferative activity, leading to reactive oxygen species occurrence and apoptosis in the human prostate cancer cells (PC‐3). Also, antiproliferative effects on human renal cancer cells were seen after administering (R)‐GTN and also (S)‐GTN (non‐natural isomer) in vitro (de Fátima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding natural product‐derived compounds, different studies have shown an antitumoral activity in different cancer cell lines treated with compounds such as GTN (de Fátima et al, ). Barcelos et al () verified that compounds derived from GTN presented antiproliferative activity, leading to reactive oxygen species occurrence and apoptosis in the human prostate cancer cells (PC‐3). Also, antiproliferative effects on human renal cancer cells were seen after administering (R)‐GTN and also (S)‐GTN (non‐natural isomer) in vitro (de Fátima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, inhibition of chronic inflammation, which precedes or accompanies tumor development, has recently come to light as an attractive option. Racemic GTN, a styryl lactone found in its R configuration in plants of the genus Goniothalamus, Annonaceae, has in vitro antiproliferative activity in human tumor cell lines via activation of apoptosis (18)(19)(20)23,38). GTN also presents general anti-inflammatory effects, without side effects (as seen with aspirin, for example) in the therapeutic doses (20,22,39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed by our group showed that racemic GTN presents gastroprotective effects, anti-inflammatory activity and inhibits the development of Ehrlich tumor (mammary adenocarcinoma) in mice (19)(20)(21)(22). Recently, we showed that GTN induces apoptosis in HT-29 colon tumor cells, which was dependent on ROS generation and caspase activation (23).…”
Section: Introductionmentioning
confidence: 96%
“…22 Piperlongumine causes an increase in reactive oxygen species (ROS) levels in cancer cells but not in normal cells, 22 and piperlongumine analogues also enhanced ROS in PC-3 cells. 24 This activity may be at least partly due to proteasome inhibition and may be responsible for the selective activity of piperlongumine. 25,26 Nonetheless, few studies to date have investigated the impact of this compound on cell migration.…”
Section: Introductionmentioning
confidence: 99%